Association between negative antithyroid peroxidase antibodies subclinical hypothyroidism and adverse perinatal outcomes diagnosed with different criteria in the third trimester of pregnancy - Golbasi, Hakan (2022)
Background: The effect of subclinical hypothyroidism (SCH) on adverse perinataloutcomes is unclear, and thyroid-stimulating hormone (TSH) reference values inpregnancy are controversial. Objective: To evaluate the effects of thyroid peroxidaseantibody (TPOAbs) negative SCH on perinatal outcomes according to the differentTSH reference values. Methods: A total of 554 pregnant women, including 509euthyroid and 45 subclinical hypothyroid (TSH > 3 mIU/L) pregnant women, wereincluded in this prospective case-controlled study. All pregnant women were inthe third trimester and were TPOAbs negative. Thyroid functions were evaluatedusing trimester-specific reference values recommended by the American Collegeof Obstetrics and Gynecology (ACOG) (TSH > 3 mIU/L) and the American ThyroidAssociation (ATA) (TSH ≥ 4 mIU/L) guidelines. Results: Neonatal mortality insubclinical hypothyroidism with a TSH upper limit of 4 mIU/L was significantly lowerthan in the euthyroid group (2 (0.4%) vs 1 (4.5%); p=0.009). There was no significantdifference in terms of adverse maternal and perinatal outcomes in SCH andeuthyroid pregnant women in both TSH reference values. There was no significantcorrelation between TSH values and delivery weeks of pregnant women with pretermdelivery (r=0.169, p=0.146). Conclusions: In this study, using different baseline TSH values recommended by the 2020 ACOG and 2017 ATAguidelines in the third trimester of pregnancy for the diagnosis of subclinical hypothyroidism, it was shown that there was no significant relationship between cases of subclinical hypothyroidism with negative TPOAbs and adverse perinatal outcomes.